PENGETAHUAN MAHASISWA TENTANG KERAHASIAAN REKAM MEDIS DI RS SANTA ELISABETH MEDAN - Adrian Martin Hutauruk (STIKes Santa Elisabeth Medan, 2019)
Interactions between health care providers and recipients or patients are closely related and can be sustainable. Medical records are very useful to assess the health status of a patient in a hospital, a clear and complete medical record will improve the quality of services and achieve optimal public health. Information about identity, diagnosis, disease history, examination history and medical history of the patient must be kept confidential by doctors, dentists, certain health personnel, management officers and leaders of health care facilities. Goals: The purpose of this study was to determine students' knowledge about the confidentiality of medical records at Santa Elisabeth Hospital, Medan. Method: This study was a descriptive observational study. The study population was students who were served at Santa Elisabeth Medan Hospital. The study sample consisted of 30 students who would in service first time in Santa Elisabeth Hospital in Medan. In this study a questionnaire was used to determine students' knowledge about the confidentiality of medical records. Data is presented descriptively to see frequency distribution. Data obtained through questionnaires filled in by samples. Results: The results showed that 66.67% of students had enough knowledge about the confidentiality of medical records. Medical record data can only be accessed by patients or families of patients responsible for patients. Conclusion: Some students have enough knowledge about the confidentiality of medical records. Students should be reminded of the confidentiality of medical records before they are served in the hospital.